Wireless, battery-free, and real-time monitoring of water permeation across thin-film encapsulation - Massimo Mariello; James Daniel Rosenthal; Francesco Cecchetti; Mingxiang Gao; Anja K. Skrivervik; Yves Leterrier; Stéphanie P. Lacour (Nature Communications, 2024)
Abstract Long-term bioelectronic implants require stable, hermetic encapsulation. Water and ion ingress are challenging to quantify, especially in miniaturized microsystems and over time. We propose a wireless and battery-free flexible platform leveraging backscatter communication and magnesium (Mg)-based microsensors. Water permeation through the encapsulation induces corrosion of the Mg resistive sensor thereby shifting the oscillation frequency of the sensing circuit. Experimental in vitro and in-tissue characterization provides information on the operation of the platform and demonstrates the robustness and accuracy of this promising method, revealing its significance for in-situ real-time monitoring of implanted bioelectronics.